TECHNICAL ANALYSIS OF SHARE PRICE MOVEMENTS TO MAKE INVESTMENT DECISIONS IN TELECOMMUNICATIONS SUB-SECTOR SHARE LISTED ON THE INDONESIA STOCK EXCHANGE - Reza Octovian (Yayasan Education and Social Center, 2023)
The long-term strategy is generally used by investors who want to buy shares of a company with the aim of holding them for a long time. To determine the right momentum to buy or sell shares in the Telecommunications sub-sector, investors need to pay attention to several factors that influence stock prices, such as market conditions, company performance, government policies, and other factors that may affect the performance of the telecommunications industry as a whole. This study aims to find out when the momentum is right to buy or sell shares in the telecommunication sub-sector. This type of research is descriptive qualitative research, with a total of 4 samples, this study uses four indicators, namely candlesticks, Moving Average, Stochastic Oscillator, and fuzzy logic. The data used in secondary data research where the data is obtained from IDX. The results of this study produce six recommendations for investment decisions in the Telecommunications sub-sector for the period January 2021 - March 2021. The movement of a company's stock price in the telecommunications industry can be influenced by various factors, including global and domestic market conditions, company performance, government policies, industry competition, and other factors that may affect the performance of the telecommunications industry as a whole